Detector Development for the CRESST Experiment - Angloher, G; Banik, S; Benato, G; Bento, A; Bertolini, A; Breier, R; Bucci, C; Burkhart, J; Canonica, L; D’Addabbo, A; Di Lorenzo, S; Einfalt, L; et al. (Springer, 2024)
Recently low-mass dark matter direct searches have been hindered by a low-energy background, drastically reducing the physics reach of the experiments. In the CRESST-III experiment, this signal is characterised by a significant increase of events below 200 eV. As the origin of this background is still unknown, it became necessary to develop new detector designs to reach a better understanding of the observations. Within the CRESST collaboration, three new different detector layouts have been developed, and they are presented in this contribution.